Menguak Budaya Curhat: Studi Perbandingan Self-disclosure pada Budaya Individualistik dan Kolektivis (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2024)
Confiding is a communication process in which someone opens up and shares their feelings, experiences or personal problems with other people. Through a psychological approach, this research discusses the phenomenon of confiding as a form of self-disclosure, where individuals voluntarily open themselves up to seek emotional support and understanding from others. Focusing on comparing individualistic and collectivistic cultures, this research discusses differences in confiding in countries with different cultures, such as America (individualist) and Indonesia (collectivist). Culture greatly influences the type of confiding, where in individualistic countries, confiding tends to be more open about personal problems, while in collectivistic countries, confiding is more related to social norms and group harmony. This research also looks at the positive impacts of self-disclosure, including emotional support, and stress management. In conclusion, confiding is not only a communication practice, but also a reflection of the complexity of social interactions in different cultural contexts.